Histological aspects and protein content of Apis mellifera L. Worker venom glands: the effect of electrical shocks in summer and winter - Abreu, R.m.m.; Moraes, R.l.m. Silva De [UNESP]; Malaspina, O. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos - CEVAP, Universidade Estadual Paulista - UNESP, 2000)
This paper analyzes the summer and winter total protein content of 7, 14, 21, 28, 35, and 40-day old Apis mellifera L. worker venom glands before (control) and 24 and 96 hours after applying electrical shocks for venom extraction (experimental). During venom extraction, 7-day old workers responded more slowly and weakly to electrical shocks. This response intensifies with age, so that the workers approaching 20 days old respond faster and more aggressively to the shocks. Statistical analysis, using the non-parametric Wilcoxon and Kruskall-Wallis tests and complemented by the Jonckheere test, showed that the protein content varied from one age to another in the experimental group, which was well distinguishable from the values in the control Group in summer and winter. Summer values at all ages were always higher than those detected in winter in both groups. This variation seems to indicate the occurrence of more than one winter glandular development cycle. Histological studies showed secretion in the lumen of the control Group secretory tubes and reservoirs. The experimental group only showed vestigial secretion in the collapsed reservoirs at all ages, except at 7 days. These workers, which reacted less efficiently to electrical shocks, showed secretion in the lumen, reservoir, and tubes, even after the application of electrical shocks. During the 96 hours following the electrical shocks, a slight protein replacement was seen at some ages. This, although higher in summer than in winter, was much lower than the level detected in the control group at all ages. The significantly lower values were frequent in the older workers 96 hours after extraction and could reflect reabsorption or degradation of proteins from glandular secretion due to aging. Our results show that venom extraction is more productive in summer using older workers. However, their capacity of replacing protein eliminated during stinging of the substrate, in response to shocks is shown to be low, as demonstrated for other analyzed bees.
Keywords: bees; histology; protein content; summer; winter; electrical shock; venom gland; Apis mellifera